ANALISIS PUTUSAN PENGADILAN NEGERI JAKARTA PUSAT NOMOR 757/PDT.G/2022/PN JKT.PST TENTANG PENUNDAAN PEMILIHAN UMUM SERENTAK TAHUN 2024 - Syanur, Fitre Nesi; Junaidi, Junaidi; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
General elections are an important pillar in a democratic country as a legitimatemechanism for changing state power, resulting in the formation of the Election Law. However, inpractice, conflicts of interest often occur which result in elections being held. The dispute raisedin this research is the PRIMA Dispute with the KPU which resulted in a decision by the CentralJakarta District Court with case registration number 757/Pdt.G/2022/PN Jkt.Pst. This decisioncontains crucial points that decide the postponement of the simultaneous general elections in2024. The aim of this thesis research is first, to analyze the absolute and relative permission ofthe Central Jakarta district court in examining and deciding the a quo case. Second, analyze theinterpretation method used in the a quo decision. Third, examine the settlement process thatshould be carried out in this case, especially the position of the Central Jakarta District Courtthat should be taken in the a quo case and the legal efforts that should be taken by PRIMA.This type of research can be classified into normative research and focuses on legalprinciples. This research uses data sources in the form of secondary data with data collectiontechniques based on literature study.From the results of research on the problem, there are three main things that can beconcluded. First, based on Law Number 7 of 2017 concerning General Elections, the CentralJakarta District Court has absolutely no absolute or relative authority in examining anddeciding a quo cases. This case clearly falls under the absolute authority of the StateAdministrative Court based on Article 470 of the Election Law and Article 2 of PERMA RINumber 2 of 2019. Second, the interpretation method used in the a quo decision is an extensiveand systematic interpretation method. Third, the resolution path that PRIMA should take is toreject the a quo case during the preliminary examination by the head of the court or give a NietOntvankelijke Verklaard (NO) decision or it cannot be accepted because there are formal defectsin the lawsuit, which is the limit of the district court's absolute authority. PRIMA can take legalaction through a lawsuit to the Jakarta PTUN with the judicial object being Bawaslu Decision002/PS.REG/BAWASLU/IX/2022.Keywords : Authority - District Court - Postponement of Elections